Reimagining Plastic Waste: The Impact of Eco-Bricking on Student Engagement and Community Sustainability - Hariswami Das (International Journal of Atmosphere, 2024)
Plastic pollution poses a severe threat to the environment, impacting ecosystems, wildlife, and human health. With millions of tons of plastic waste generated globally each year, innovative solutions for waste management are essential. This paper explores the eco-bricking initiative at Sovanagar High School, which transforms plastic waste into eco-bricks—sustainable building materials used for constructing green walls, benches, and other structures on the school campus. By effectively reducing plastic waste, this initiative not only mitigates the environmental impact of discarded plastics but also promotes sustainable development practices within the educational institution.The eco-bricking program has been successful in engaging students creatively in environmental problem-solving, fostering a sense of responsibility and stewardship towards the planet. Students are encouraged to collect plastic waste from their surroundings and participate in workshops where they learn how to create eco-bricks. This hands-on experience not only empowers them with practical skills but also instills a deeper understanding of the implications of plastic pollution and the importance of recycling.Furthermore, the school’s anti-plastic campaign, launched on World Environment Day in 2019, extends these efforts beyond the campus into the broader community. The campaign includes a large-scale cleanup drive aimed at reducing single-use plastic consumption within the local area. Educational outreach initiatives are also an integral part of this campaign, as students engage with community members to raise awareness about the harmful effects of plastic pollution and the importance of sustainable practices.Incentives such as fee waivers for participating students have significantly increased engagement in both the eco-bricking initiative and the anti-plastic campaign, highlighting the importance of sustainability and community involvement. By combining education, hands-on experience, and community outreach, Sovanagar High School demonstrates a comprehensive approach to tackling plastic pollution.This paper highlights the program’s impact on reducing plastic waste and its broader role in promoting sustainable practices among students and the local community. By serving as a model for other schools and communities, the eco-bricking initiative at Sovanagar High School illustrates how grassroots efforts can contribute to significant environmental change, inspiring a new generation of environmentally conscious citizens dedicated to preserving our planet for future generations.
Keywords: Eco-bricking; Environmental education; Plastic waste management; Sustainability; community engagement; eco-friendly initiatives